Method for improving polycrystalline perovskite crystal quality through solid-solid imprinting annealing
Through solid-solid imprinting annealing method, the solid imprinting layer of pyridine molecules is covered and annealed on the surface of the perovskite wet film, solving the problem of structural degradation of perovskite film at high temperatures, and significantly improving the efficiency and stability of perovskite solar cells.
Patent Information
- Application Number
- CN202411605672.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-11-12
AI Technical Summary
The traditional perovskite annealing process leads to structural degradation of perovskite films at high temperatures, forming crystal defects, and affecting the efficiency and stability of solar cells.
The solid-solid imprint annealing method is adopted to cover the solid-state imprint layer of pyridine molecules on the surface of the perovskite wet film and anneale under certain pressure and temperature conditions to inhibit structural degradation and improve crystal quality.
It effectively improves the crystallinity and flatness of perovskite films, and enhances the photoelectric conversion efficiency and long-term stability of solar cells.
Smart Images

Figure CN119789751A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of photovoltaic technology, and in particular to a method for improving the quality of polycrystalline perovskite crystals by solid-solid imprint annealing. Background Art
[0002] As a clean and renewable energy source, solar energy has received widespread attention from countries around the world. In recent decades, new perovskite photovoltaic technology has made significant progress. Compared with traditional crystalline silicon solar cells, perovskite solar cells (PSCs) have excellent photoelectric conversion efficiency, more economical manufacturing costs, low-energy consumption preparation processes, and flexible and diverse application forms. They are considered to be one of the new generation of photovoltaic technologies with the most promising commercial applications.
[0003] There are many defects (such as vacancies, interstitials, rearrangements, etc.) in polycrystalline perovskite films prepared by solution method, especially on the surface and grain boundaries of perovskite, which lead to serious non-radiative carrier recombination, ion migration, perovskite degradation, etc., restricting the efficiency and stability of the device. The formation of these defects is closely related to the perovskite annealing process. The traditional high-temperature thermal annealing process can promote the diffusion and rearrangement of perovskite component ions or molecules, which is conducive to the formation of crystal nuclei and crystal growth. Appropriate annealing conditions can improve the integrity and regularity of perovskite crystals. However, studies have found that even if the perovskite precursors of organic ammonium salts and lead iodide are used in equal stoichiometric ratios, lead iodide (PbI2) will be enriched on the surface or grain boundaries of the annealed perovskite. This is because the perovskite will undergo surface micro-degradation during high-temperature annealing - the surface defects caused by heating cause the collapse of the perovskite crystal structure. In addition, the thermal annealing process will also cause many crystal defects in perovskite, among which iodine vacancy defects are extremely common. Researchers generally use various passivators such as Lewis acids and bases, halide salts, ionic liquids and organic small molecules to passivate defects in perovskite films. These passivation methods can achieve a certain defect repair effect, but they directly ignore the degradation behavior of perovskite during annealing and cannot fundamentally solve the problem.
[0004] In addition, the traditional passivation method is to cover the polycrystalline perovskite film with a passivating agent as a whole to construct a two-dimensional / three-dimensional perovskite heterojunction structure, resulting in most of the perovskite surfaces that do not need to be passivated also being covered with passivating materials. These insulating two-dimensional layered structures will hinder the transmission of carriers and restrict the photovoltaic performance of perovskite solar cells. Therefore, seeking a more efficient, more controllable, and more universal perovskite annealing process is particularly important for promoting the development of high-quality perovskite solar cells. Summary of the invention
[0005] To solve the above problems, the present invention provides a simple, efficient and universal solid-solid imprint annealing method to inhibit the structural degradation of polycrystalline perovskite films due to surface defects during traditional thermal annealing, improve the crystallinity and film quality of perovskite, and further improve the photoelectric conversion efficiency and long-term stability of perovskite solar cells.
[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0007] A method for improving the quality of polycrystalline perovskite crystals by solid-solid imprint annealing, first preparing a pyridine molecule solid imprint layer, then covering the solid imprint layer on the surface of the perovskite wet film at the initial stage of perovskite annealing, and annealing is performed under certain pressure and temperature conditions until the annealing process is completed.
[0008] As a possible implementation, further, the N and (CH2) in the pyridine molecule x NH2 is in the adjacent position, and any one of 2-aminopyridine, 2-aminomethylpyridine, 2-(2-aminoethyl)pyridine and the like is selected.
[0009] As a possible implementation mode, further, the initial annealing period is 1 to 5 minutes from the beginning of annealing, the annealing temperature is 120 to 150° C., the total annealing time is 10 to 30 minutes, and the pressure is 0.049 to 0.1225 MPa.
[0010] As a possible implementation mode, further, the method for improving the quality of polycrystalline perovskite crystals by solid-solid imprint annealing specifically comprises the following steps:
[0011] 1) Processing conductive glass: cutting the conductive glass into required sizes and cleaning it for later use;
[0012] 2) Preparing a tin dioxide electron transport layer: preparing a raw material solution, and preparing a tin dioxide film on the glass treated in step 1) by a chemical bath deposition method;
[0013] 3) preparing a pyridine solid imprint layer: preparing a pyridine isopropanol solution, coating a pyridine molecular layer on the glass surface treated in step 1), and then performing an annealing treatment;
[0014] 4) Preheating of the stamping weight: Place the weight on a hot table for preheating;
[0015] 5) Preparing a perovskite film: preparing a perovskite precursor solution, and dropping it onto the substrate treated in step 2) to prepare a wet film;
[0016] 6) Solid-solid imprint annealing: Under heating conditions, the pyridine solid imprint layer prepared in step 3) is covered on the upper surface of the perovskite film, and then the weight preheated in step 4) is pressed on the covering layer. Solid-solid imprinting is performed at the beginning of perovskite annealing until the perovskite annealing is completed, and the imprint layer is removed.
[0017] As a possible implementation mode, further, the method for improving the quality of polycrystalline perovskite crystals by solid-solid imprint annealing further includes:
[0018] 7) Preparation of Spiro-OMeTAD hole transport layer: Prepare a Spiro-OMeTAD chlorobenzene solution, apply it on the perovskite film prepared in step 6), and then place the film in a constant temperature and humidity drying oven for oxidation treatment;
[0019] 8) Preparation of metal counter electrode: Depositing a metal counter electrode with high work function on the Spiro-OMeTAD film treated in step 7) by vacuum thermal evaporation.
[0020] As a possible implementation, further, the conductive glass substrate in step 1) is selected from any one of flexible substrates such as indium tin oxide (ITO), fluorine-doped tin oxide (FTO), polyester (PET / ITO, PEN / ITO), etc., and the square resistance is 5 to 20 Ω / cm 2 ; The cleaning steps of conductive glass include:
[0021] The glass is ultrasonically cleaned with glass cleaning liquid, deionized water, acetone, ethanol and isopropanol in sequence, and then treated with a UV-ozone cleaning machine after drying; the ultrasonic cleaning time is 15 to 20 minutes; the UV-ozone cleaning machine treatment time is 15 to 30 minutes, and the temperature is 20 to 30°C.
[0022] As a possible implementation, further, the preparation method of the raw material solution in step 2) is: dissolving 2g urea, 2mL hydrochloric acid, 40uL trifluoroacetic acid and 0.44g SnCl2·2H2O in 160mL deionized water;
[0023] The chemical bath deposition method comprises the following steps: immersing the conductive glass substrate in a raw material solution, reacting the solution at 90° C. for 4 hours, taking out the glass, ultrasonically cleaning it with deionized water and isopropanol for 5 minutes respectively, then rinsing it with deionized water and ethanol, and then drying it with a nitrogen flow.
[0024] As a possible implementation, further, the pyridine concentration in the pyridine isopropanol solution in step 3) is 0.08-0.42 mol / L, and the optimal concentration is 0.25 mol / L; the preparation method is: take an appropriate amount of pyridine molecules and dissolve them in 1 mL of isopropanol, and stir and mix them evenly;
[0025] The pyridine isopropanol solution is applied to the glass surface treated in step 1) by spin coating or immersion;
[0026] The spin coating method is as follows: 50uL of pyridine isopropanol solution is added dropwise to the glass surface for spin coating to form a film; the spin coating speed is 500-3000rpm, and the spin coating time is 30-50s; the immersion method is as follows: the glass is immersed in the pyridine isopropanol solution for 1-5min;
[0027] The annealing temperature is 80-120° C., and the annealing time is 5 minutes.
[0028] As a possible implementation, further, the weight in step 4) is a chrome-plated weight with good thermal conductivity; the weight mass is 2-5 kg, so as to adjust the size of the imprinting force; the preheating temperature is 120-150° C., and the preheating time is 3-5 min;
[0029] In step 5), the perovskite precursor solution is dripped onto the substrate treated in step 2), and a one-step anti-solvent method is used to spin-coat the substrate to form a film; wherein the spin-coating speed is 1000-5000 rpm, the spin-coating time is 10-50 s, and the anti-solvent is ether or chlorobenzene;
[0030] The concentration of the perovskite precursor solution is 1.5-1.8 mol / L; the solvent system is a mixed solvent of DMF and DMSO, and the volume ratio of DMF:DMSO is 4:1-9:1;
[0031] The perovskite component is any one of formamidinium iodide-based perovskite (FAPbI3), methylammonium iodide-based perovskite (MAPbI3), cesium-based perovskite (CsPbI3) or ternary mixed perovskite.
[0032] As a possible implementation, further, the preparation method of the Spiro-OMeTAD chlorobenzene solution in step 7) is: 73.2 mg Spiro-OMeTAD is dissolved in 1 mL chlorobenzene and stirred for 1 h, and then 28.8 μL 4-tert-butylpyridine and 17.6 μL 520 mg mL -1 The solution of LiTFSI in acetonitrile was stirred for 1 h;
[0033] The spin coating speed is 3000 rpm, the spin coating time is 30 seconds; the drying oven temperature is 20-25°C, the humidity is 10-20%, and the oxidation time is 20 hours;
[0034] In step 8), the metal is Au or Ag; the evaporation rate is 0.005-0.2 nm / s, the evaporation temperature is 900-1000° C., the evaporation time is 20-30 min, and the electrode thickness is 60-90 nm.
[0035] The beneficial effects of the present invention are as follows:
[0036] Compared with the traditional perovskite annealing method, the solid-solid imprint annealing method provided by the present invention has the following advantages:
[0037] 1) Delay the volatilization of solvents, reduce the migration speed of perovskite components, provide enough time for perovskite crystal growth, and promote the formation of large grains. At the same time, guide the solvent to migrate horizontally, so that the perovskite wet film can grow epitaxially and orderly in a limited space, improve the regularity and orderliness of perovskite crystals, and improve the flatness of perovskite films.
[0038] 2) Apply the same annealing temperature to the upper and lower sides of the perovskite film to keep the crystal growth environment at the upper and lower interfaces of the perovskite consistent, promote the synchronous growth of perovskite crystals at the upper and lower interfaces, and improve the overall quality of the perovskite film.
[0039] 3) Pyridine molecules are introduced in the form of a solid imprint layer to avoid the damage of organic solvents to the upper surface of perovskite in the traditional pyridine passivation method. At the same time, the iodine vacancy defects, iodine interstitial defects and uncoordinated lead ion defects generated on the surface of polycrystalline perovskite are precisely coordinated to avoid excess pyridine molecules covering the perovskite surface, achieving high-efficiency and high-selectivity passivation.
[0040] 4) It is applicable to perovskite films and perovskite systems of different areas. The immersion preparation method of the solid-state imprint layer can match perovskite films of different areas, and has large-scale application prospects. In addition, the solid-state imprint layer can be used repeatedly, and the effect of multiple solid-solid imprint annealing treatments on perovskite films is the same, which is conducive to reducing the cost of passivation materials and improving the commercial application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 The figure is a schematic diagram of the preparation of the pyridine solid imprint layer and the solid-solid imprint annealing process;
[0042] Figure 2 Scanning electron micrographs of the perovskite film surfaces prepared by conventional annealing (without pyridine molecules), conventional annealing (2-(2-aminoethyl)pyridine), and solid-solid imprint annealing (2-(2-aminoethyl)pyridine);
[0043] Figure 3 In-situ grazing incidence wide-angle X-ray scattering images of the perovskite film surface prepared by conventional annealing and solid-solid imprint annealing;
[0044] Figure 4 Photoluminescence mapping of perovskite films prepared by conventional annealing and solid-solid imprint annealing;
[0045] Figure 5Current density-voltage forward and reverse sweep curves of perovskite solar cells (active area 0.1 cm2) prepared by conventional annealing and solid-solid imprint annealing;
[0046] Figure 6 Stability test of devices prepared by conventional annealing and solid-solid imprint annealing at maximum power point (MPP tracking);
[0047] Figure 7 Scanning electron micrograph of the surface of the perovskite film prepared by the solid-solid imprinting method after preparing the solid-imprinting layer by spin coating and immersion method;
[0048] Figure 8 Large area (effective area 1cm) prepared by solid-solid imprint annealing 2 ) Current density-voltage forward and reverse sweep curves of perovskite solar cells;
[0049] Fig. 9 The device efficiency statistics are shown in Figure 1. ...
[0050] Fig.10 Scanning electron microscope images of the surface of perovskite films with different components prepared by solid-solid imprinting method. DETAILED DESCRIPTION
[0051] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0052] See attached Figure 1 As shown, the present invention provides a method for improving the quality of polycrystalline perovskite crystals by solid-solid imprint annealing, and the specific steps are as follows:
[0053] 1) Treating the conductive glass: Cut the conductive glass into standard sizes, and ultrasonically clean it with glass cleaning liquid, deionized water, acetone, ethanol and isopropanol in turn, blow dry it, and then treat it with a UV-ozone cleaning machine for 15 to 30 minutes at a temperature of 20 to 30°C, and collect it for later use; wherein the conductive glass substrate is one of the flexible substrates such as indium tin oxide (ITO), fluorine-doped tin oxide (FTO), polyester (PET / ITO, PEN / ITO), etc., and the square resistance is 5 to 20Ω / cm 2 .
[0054] 2) Preparing a tin dioxide electron transport layer: dissolving 2 g of urea, 2 mL of hydrochloric acid, 40 uL of trifluoroacetic acid and 0.44 g of SnCl2·2H2O in 160 mL of deionized water to prepare a raw material solution; using a chemical bath deposition method to prepare a tin dioxide film on the glass treated in step 1); wherein the chemical bath deposition method is as follows: immersing a glass substrate in the raw material solution, reacting at 90° C. for 4 h, then taking out the glass, ultrasonically cleaning it with deionized water and isopropanol for 5 min respectively, then rinsing it with deionized water and ethanol, and then drying it with a nitrogen flow.
[0055] 3) Prepare a pyridine solid imprint layer: take an appropriate amount of pyridine molecules and dissolve them in 1mL of isopropanol, stir and mix evenly to obtain a pyridine isopropanol solution, the pyridine concentration is 0.08-0.42mol / L; coat the pyridine molecule layer on the glass surface treated in step 1), and then anneal it, the annealing temperature is 80-120℃, and the annealing time is 5min. Among them, the coating method includes spin coating and immersion method, so that it can meet the needs of small-scale laboratory and large-scale applications; the spin coating method is: take 50uL of pyridine isopropanol solution, add it dropwise to the glass surface for spin coating to form a film; the spin coating speed is 500-3000rpm, and the spin coating time is 30-50s. The immersion method is: immerse the glass in the pyridine isopropanol solution for 1-5min.
[0056] 4) Preheating of the stamping weight: Place the freshly chrome-plated weight (the weight mass is 2-5 kg, so as to adjust the stamping force) on a hot table for preheating. The preheating temperature is 120-150°C and the preheating time is 3-5 minutes.
[0057] 5) Preparation of perovskite film: preparing a 1.5-1.8 mol / L perovskite precursor solution, wherein the solvent system of the perovskite precursor solution is a mixed solvent of DMF and DMSO, the volume ratio of DMF:DMSO is 4:1-9:1, and the perovskite component is any one of formamidinium iodide perovskite (FAPbI3), methylammonium iodide perovskite (MAPbI3), cesium perovskite (CsPbI3) or ternary mixed perovskite
[0058] Then, in a glove box, the above solution is dripped onto the substrate treated in step 2), and a film is formed by spin coating using a one-step anti-solvent method, with a spin coating speed of 1000-5000 rpm and a spin coating time of 10-50 s; wherein the anti-solvent is ether or chlorobenzene.
[0059] 6) Solid-solid imprint annealing: The perovskite wet film in step 5) is transferred to a hot stage, the pyridine solid imprint layer prepared in step 3) is covered on the upper surface of the perovskite, and then the preheated weight in step 4) is pressed on the covering layer (the pressure is 0.049-0.1225 MPa), and solid-solid imprinting is performed at the initial stage of perovskite annealing (the initial stage of annealing is 1-5 minutes from the beginning of annealing) until the perovskite annealing is completed, and the imprint layer is removed; the annealing temperature during this period is 120-150°C; the total annealing time is 10-30 minutes.
[0060] 7) Preparation of Spiro-OMeTAD hole transport layer: 73.2 mg Spiro-OMeTAD was dissolved in 1 mL chlorobenzene and stirred in a glove box for 1 h; 28.8 μL 4-tert-butylpyridine and 17.6 μL LiTFSI in acetonitrile (520 mg mL -1 ), and continue stirring for 1 h to prepare a Spiro-OMeTAD chlorobenzene solution to obtain a Spiro-OMeTAD chlorobenzene solution;
[0061] The Spiro-OMeTAD chlorobenzene solution was spin-coated on the perovskite film prepared in step 6) at a spin-coating speed of 3000 rpm for 30 seconds; the film was then placed in a constant temperature and humidity drying oven at a temperature of 20-25°C and a humidity of 10-20% for oxidation treatment for 20 hours.
[0062] 8) Preparation of metal counter electrodes: Depositing high work function metal (Au or Ag) counter electrodes on the Spiro-OMeTAD film treated in step 7) by vacuum thermal evaporation; wherein the evaporation rate is 0.005-0.2 nm / s, the evaporation temperature is 900-1000°C, the evaporation time is 20-30 min, and the electrode thickness is 60-90 nm.
[0063] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0064] Embodiment 1:
[0065] In this embodiment, a 2-(2-aminoethyl)pyridine solid imprint layer is prepared by spin coating, and a perovskite film is prepared by solid-solid imprinting method, and then a perovskite solar cell (effective area 0.1 cm) is assembled. 2 ). The specific steps are as follows:
[0066] (1) Processing of ITO conductive glass substrate: This embodiment uses a sheet resistance of 12Ω / cm 2 ITO is used as the substrate. First, ITO is cut into 2x2cm 2The standard size was laser etched. Then, glass cleaning liquid, deionized water, acetone, ethanol and isopropanol were ultrasonically treated for 15 minutes respectively, and compressed air was used to blow dry. Finally, a UV-ozone cleaning machine was used to clean the glass at room temperature for 20 minutes.
[0067] (2) Preparation of tin dioxide electron transport layer: 2 g urea, 2 mL hydrochloric acid, 40 uL trifluoroacetic acid and 0.44 g SnCl2·2H2O were dissolved in 160 mL deionized water and stirred to mix well. The ITO obtained in step (1) was immersed in the above raw material solution, reacted at 90°C for 4 h, then taken out, ultrasonically cleaned with deionized water and isopropanol for 5 min respectively, then rinsed with distilled water and ethanol, and then dried by nitrogen flow.
[0068] (3) The method for preparing the 2-(2-aminoethyl)pyridine solid imprint layer is as follows: prepare 1 mL of 0.25 mol / L 2-(2-aminoethyl)pyridine isopropanol solution, take 50 uL of the above solution, drop it on the ITO substrate obtained in step (1), and spin coat it to form a film. The spin coating speed is 1000 rpm and the spin coating time is 30 s. Then anneal at 100° C. for 5 min. At this time, place a fresh chrome-plated weight with a weight of 2 kg on a hot plate at 150° C. for 3 min.
[0069] (4) Preparation of FAPbI3 perovskite light-absorbing layer: Weigh 265 mg FAI, 710 mg PbI2 and 15 mg MACl and dissolve them in 1 mL of DMF / DMSO (v:v=8:1) mixed solvent, stir overnight, and then filter the above solution with a PTFE filter head (0.45 μm). Prepare the perovskite film in a glove box, take 50 uL of the above solution and drop it on the glass substrate obtained in step (2), and spin coat it into a film. Specifically, first spin coat at a spin coating speed of 1000 rpm and a spin coating time of 10 s, and then spin coat at a spin coating speed of 5000 rpm and a spin coating time of 30 s for one-step spin coating. In the last 15 s of the spin coating process, quickly drop 700 uL of ether onto the perovskite film. After the spin coating is completed, transfer the glass to a hot plate at 150°C for annealing.
[0070] (5) Solid-solid imprint annealing process: At the 3rd minute of the annealing of the perovskite film, the solid imprint layer obtained in step (3) is covered on the upper surface of the perovskite obtained in step (4), and then the weight preheated in step (3) is pressed onto the covering layer, and the imprint annealing is continued. The pressure is 0.049 MPa, the annealing temperature is 150°C, and the total annealing time is 15 minutes. After the annealing is completed, the weight is removed and the film is naturally cooled to room temperature.
[0071] (6) Preparation of Spiro-OMeTAD hole transport layer: 73.2 mg of Spiro-OMeTAD was weighed in a glove box and dissolved in 1 mL of chlorobenzene. The mixture was stirred at room temperature for 1 h. Then 28.8 μL of 4-tert-butylpyridine and 17.6 μL of LiTFSI in acetonitrile (520 mg mL -1 ), and continue stirring for 1 hour. Take 30uL of Spiro-OMeTAD chlorobenzene solution and drop it on the perovskite film obtained in step (5), and spin-coat it into a film. The spin-coating speed is 3000rmp and the spin-coating time is 30s. Then transfer the glass to a constant temperature and humidity chamber at a temperature of 25°C and a humidity of 15% for oxidation for 20 hours.
[0072] (7) Preparation of Au counter electrode: 100 mg of Au was placed in a vacuum thermal evaporator to prepare a counter electrode on the film obtained in step (6). The evaporation rate was 0.05 nm / s, the evaporation temperature was 900-1000° C., the evaporation time was 20-30 min, and the thickness of the counter electrode was 80 nm.
[0073] Embodiment 2:
[0074] In this embodiment, a 2-(2-aminoethyl)pyridine solid-state imprint layer is prepared by an immersion method, and a perovskite film is prepared by a solid-solid imprint method, and then a perovskite solar cell is assembled.
[0075] The preparation method of this embodiment is basically the same as that of Example 1, except for step (3). In this embodiment, step (3) prepares a 2-(2-aminoethyl)pyridine solid imprint layer: prepare 10 mL of 0.25 mol / L 2-(2-aminoethyl)pyridine isopropanol solution, pour the solution into a culture dish, and then put the ITO substrate obtained in step (1) into the culture dish and soak for 3 minutes, then take it out and anneal it at 100°C for 5 minutes. At this time, place a 2 kg chrome-plated weight on a hot plate at 150°C for 3 minutes. Other specific steps are the same as in Example 1.
[0076] Embodiment 3:
[0077] In this embodiment, a 2-(2-aminoethyl)pyridine solid imprint layer is prepared by an immersion method, and a perovskite film is prepared by a solid-solid imprint method, and then a large area (effective area 1cm 2 )Perovskite solar cells.
[0078] The size of the ITO glass used in step (1) of this embodiment is 2x2cm 2 , can also be enlarged to 5x5cm 2 , 10x10cm 2 The effective area of the subcell prepared in step (7) is 1 cm 2, and can also be enlarged to a battery with a larger effective area. Other specific steps are the same as in Example 2.
[0079] Embodiment 4:
[0080] In this embodiment, a 2-(2-aminoethyl)pyridine solid imprint layer is prepared by spin coating, and then the same solid imprint layer is used to perform multiple solid-solid imprint annealing to assemble a perovskite solar cell.
[0081] In this embodiment, step (4) is repeated to prepare multiple (~30) FAPbI3 perovskite light absorbing layers, and when each perovskite is annealed, the same 2-(2-aminoethyl)pyridine solid imprint layer prepared in step (3) is used for solid-solid imprint annealing. Other specific steps are the same as in Example 1.
[0082] Embodiment 5:
[0083] In this embodiment, a 2-(2-aminoethyl)pyridine solid imprint layer is prepared by spin coating, and a MAPbI3 perovskite film is prepared by solid-solid imprinting method, and then a perovskite solar cell is assembled.
[0084] In the present embodiment, the method for preparing the MAPbI3 perovskite light-absorbing layer in step (4) is as follows: prepare a MAPbI3 precursor solution with a molar ratio of PbI2 and MAl of 1:1, dissolve it in 1 mL of a mixed solvent of DMF / DMSO (v:v=7:3), and the solution concentration is 1.2 mol / L. Stir overnight, and then filter the above solution with a PTFE filter head (0.45 μm). Prepare a perovskite film in a glove box, take 50 uL of the above solution and drop it on the glass substrate obtained in step (2), and spin coat it into a film. Specifically, a rotation speed of 4000 rpm and a rotation time of 60 s are used, and 260 uL of chlorobenzene antisolvent is quickly dripped onto the perovskite film at 25 s. After the spin coating is completed, the glass is transferred to a hot plate at 120°C for annealing. The other specific steps are the same as in Example 1.
[0085] Embodiment 6:
[0086] In this embodiment, a spin coating method is used to prepare a 2-(2-aminoethyl)pyridine solid imprint layer, and a solid-solid imprint method is used to prepare Cs x FA 1-x PbI3 perovskite film, and then assemble perovskite solar cells.
[0087] In this embodiment, step (4) prepares Cs x FA 1-x The method of the PbI3 perovskite light absorbing layer is as follows: prepare CsI with a molar ratio of FAI, CsI and PbI2 of 1.3:0.065:1.365 x FA 1-xThe PbI3 precursor solution is dissolved in 1 mL of a DMF / DMSO (v:v=4:1) mixed solvent, and the solution concentration is 1.4 mol / L. Stir overnight, and then filter the above solution with a PTFE filter head (0.45 μm). Prepare a perovskite film in a glove box, take 50uL of the above solution and drop it on the glass substrate obtained in step (2), and spin coat it into a film. Specifically, first spin coat at a spin coating speed of 1000 rpm and a spin coating time of 10s, and then spin coat at a spin coating speed of 5000 rpm and a spin coating time of 30s for one-step spin coating. In the last 15s of the spin coating process, quickly drop 260uL of chlorobenzene antisolvent onto the perovskite film. After the spin coating is completed, transfer the glass to a hot plate at 150°C for annealing. The other specific steps are the same as in Example 1.
[0088] Embodiment 7:
[0089] In this embodiment, a spin coating method is used to prepare a 2-(2-aminoethyl)pyridine solid imprint layer, and a solid-solid imprint method is used to prepare MA x FA 1-x Pb(I y Br 1-y )3 perovskite film, and then assemble perovskite solar cells.
[0090] In this embodiment, step (4) prepares MA x FA 1-x Pb(I y Br 1-y )3 The method of perovskite light absorbing layer is: prepare MA with a molar ratio of FAPbI3 and MAPbBr3 of 0.95:0.05 x FA 1-x Pb(I y Br 1-y )3 precursor solution, dissolved in 1mL of DMF / DMSO (v:v=8:1) mixed solvent, the solution concentration is 1.4mol / L. Stir overnight, and then filter the above solution with a PTFE filter head (0.45μm). Prepare the perovskite film in a glove box, take 50uL of the above solution and drop it on the glass substrate obtained in step (2), and spin coat it into a film. Specifically, first spin coat at a spin coating speed of 1000rpm and a spin coating time of 10s, and then spin coat at a spin coating speed of 5000rpm and a spin coating time of 30s for one-step spin coating. In the last 15s of the spin coating process, quickly drop 700uL of ether anti-solvent onto the perovskite film. After the spin coating is completed, transfer the glass to a hot plate at 150°C for annealing. The other specific steps are the same as Example 1.
[0091] Comparative Example 1:
[0092] This embodiment uses a traditional annealing method to prepare a perovskite film and then assemble a perovskite solar cell. The specific steps are as follows:
[0093] (1) Processing of ITO conductive glass substrate: This embodiment uses a sheet resistance of 12Ω / cm 2 The ITO is a conductive glass substrate. First, cut the ITO into 2x2cm 2 The standard size was laser etched. Then, glass cleaning liquid, deionized water, acetone, ethanol and isopropanol were ultrasonically treated for 15 minutes respectively, and compressed air was used to blow dry. Finally, a UV-ozone cleaning machine was used to clean the glass at room temperature for 20 minutes.
[0094] (2) Preparation of tin dioxide electron transport layer: 2 g urea, 2 mL hydrochloric acid, 40 uL trifluoroacetic acid and 0.44 g SnCl2·2H2O were dissolved in 160 mL deionized water and stirred to mix well. The ITO obtained in step (1) was immersed in the above raw material solution, reacted at 90°C for 4 h, then taken out, ultrasonically cleaned with deionized water and isopropanol for 5 min respectively, then rinsed with distilled water and ethanol, and then dried by nitrogen flow.
[0095] (3) Preparation of FAPbI3 perovskite light-absorbing layer: Weigh 265 mg FAI, 710 mg PbI2 and 15 mg MACl and dissolve them in 1 mL of DMF / DMSO (v:v=8:1) mixed solvent, stir overnight, and then filter the above solution with a PTFE filter head (0.45 μm). Prepare the perovskite film in a glove box, take 50 uL of the above solution and drop it on the glass substrate obtained in step (2), and spin coat it into a film. Specifically, first spin coat at a spin coating speed of 1000 rpm and a spin coating time of 10 s, and then spin coat at a spin coating speed of 5000 rpm and a spin coating time of 30 s for one-step spin coating. In the last 15 s of the spin coating process, quickly drop 700 uL of ether anti-solvent onto the perovskite film. After the spin coating is completed, transfer the glass to a hot plate at 150°C for annealing for 15 min and cool it naturally to room temperature.
[0096] (4) Preparation of Spiro-OMeTAD hole transport layer: 73.2 mg of Spiro-OMeTAD was weighed in a glove box, dissolved in 1 mL of chlorobenzene, and stirred for 1 h. Then 28.8 μL of 4-tert-butylpyridine and 17.6 μL of LiTFSI in acetonitrile (520 mg mL -1 ), continue stirring for 1 hour. Take 30uL of Spiro-OMeTAD chlorobenzene solution and drop it on the perovskite film obtained in step (3) for spin coating. The spin coating speed is 3000rmp and the spin coating time is 30s. Then transfer the glass to a constant temperature and humidity chamber at a temperature of 25°C and a humidity of 15% for oxidation for 20 hours.
[0097] (5) Preparation of Au counter electrode: 100 mg Au was placed in a vacuum thermal evaporator, and an Au counter electrode was deposited on the thin film obtained in step (4) with a thickness of 80 nm at a deposition rate of 0.05 nm / s, a deposition temperature of 900-1000°C, and a deposition time of 20-30 min.
[0098] Comparative Example 2:
[0099] This embodiment uses a conventional annealing method to prepare a perovskite film, and then spin-coats 2-(2-aminoethyl)pyridine molecules on the perovskite surface for passivation, and then assembles a perovskite solar cell. The specific steps are as follows:
[0100] (1) Processing of ITO conductive glass substrate: This embodiment uses a sheet resistance of 12Ω / cm 2 The ITO is a conductive glass substrate. First, cut the ITO into 2x2cm 2 The standard size was laser etched. Then, glass cleaning liquid, deionized water, acetone, ethanol and isopropanol were ultrasonically treated for 15 minutes respectively, and compressed air was used to blow dry. Finally, a UV-ozone cleaning machine was used to clean the glass at room temperature for 20 minutes.
[0101] (2) Preparation of tin dioxide electron transport layer: 2 g urea, 2 mL hydrochloric acid, 40 uL trifluoroacetic acid and 0.44 g SnCl2·2H2O were dissolved in 160 mL deionized water and stirred to mix well. The ITO obtained in step (1) was immersed in the above raw material solution, reacted at 90°C for 4 h, then taken out, ultrasonically cleaned with deionized water and isopropanol for 5 min respectively, then rinsed with distilled water and ethanol, and then dried by nitrogen flow.
[0102] (3) Preparation of FAPbI3 perovskite light-absorbing layer: Weigh 265 mg FAI, 710 mg PbI2 and 15 mg MACl and dissolve them in 1 mL of DMF / DMSO (v:v=8:1) mixed solvent, stir overnight, and then filter the above solution with a PTFE filter head (0.45 μm). Prepare the perovskite film in a glove box, take 50 uL of the above solution and drop it on the glass substrate obtained in step (2), and spin coat it into a film. Specifically, first spin coat at a spin coating speed of 1000 rpm and a spin coating time of 10 s, and then spin coat at a spin coating speed of 5000 rpm and a spin coating time of 30 s for one-step spin coating. In the last 15 s of the spin coating process, quickly drop 700 uL of ether anti-solvent onto the perovskite film. After the spin coating is completed, transfer the glass to a hot plate at 150°C for annealing for 15 min and cool it naturally to room temperature.
[0103] (4) Passivation of the perovskite surface: Weigh 3 mg of 2-(2-aminoethyl)pyridine molecules, dissolve them in 1 mL of isopropanol solution, and stir thoroughly to dissolve. Prepare a perovskite surface passivation layer in a glove box. Take 50 uL of the above solution and drop it onto the perovskite surface obtained in step (3), and spin coat it to form a film. Specifically, the spin coating speed is 4000 rpm and the spin coating time is 30 s, and one-step spin coating is performed. After the spin coating is completed, the perovskite is transferred to a hot plate at 100°C for annealing for 5 minutes, and then naturally cooled to room temperature.
[0104] (5) Preparation of Spiro-OMeTAD hole transport layer: 73.2 mg of Spiro-OMeTAD was weighed in a glove box and dissolved in 1 mL of chlorobenzene and stirred for 1 h. Then 28.8 μL of 4-tert-butylpyridine and 17.6 μL of LiTFSI in acetonitrile (520 mg mL -1 ), and continue stirring for 1 hour. Take 30uL of Spiro-OMeTAD chlorobenzene solution and drop it on the perovskite film obtained in step (4) for spin coating. The spin coating speed is 3000rmp and the spin coating time is 30s. Then transfer the glass to a constant temperature and humidity chamber at a temperature of 25°C and a humidity of 15% for oxidation for 20 hours.
[0105] (6) Preparation of Au counter electrode: 100 mg Au was placed in a vacuum thermal evaporator, and an Au counter electrode was deposited on the thin film obtained in step (5) with a thickness of 80 nm at a deposition rate of 0.05 nm / s, a deposition temperature of 900-1000°C, and a deposition time of 20-30 min.
[0106] Performance Testing
[0107] Compared with Comparative Examples 1 and 2, Examples 1-7 all achieved good perovskite film quality and device performance optimization effects. Specifically, when the conventional spin coating method is used for annealing ( Figure 2 Left, Comparative Example 1) or when the pyridine passivation layer is introduced alone by solution spin coating ( Figure 2 In Example 2), enriched lead iodide can be clearly detected on the surface of the perovskite film, the perovskite grain boundary is not obvious, and the film uniformity is poor. However, no lead iodide appears on the surface of the perovskite film prepared by the solid-solid embossing method (Example 1), the perovskite grains are larger, the crystals are more complete and uniform, and the stacking is more compact ( Figure 2 Right), indicating that the solid-solid imprinting method can significantly inhibit the precipitation of lead iodide, fundamentally solve the surface micro-degradation of perovskite during high-temperature annealing, and effectively improve the crystal quality of perovskite. The crystallinity of perovskite ( Figure 3 ) and photoluminescence intensity ( Figure 4 ) have been significantly improved, and the efficiency of perovskite photovoltaic devices prepared by solid-solid imprinting method has increased from 24.44% to 26.22% ( Figure 5 ), the maximum power output stability reaches 1350 hours ( Figure 6 ).
[0108] To further verify the scalability of the solid-solid imprinting method, the present invention applies the solid-solid imprinting method to different process flows, and obtains good device photovoltaic performance. Specifically, the pyridine solid layer is prepared by the immersion method (Example 2), and then the solid-solid imprinting annealing is performed. The perovskite film shows a microscopic morphology similar to that of the spin coating perovskite film (Example 1) ( Figure 7 ), the device efficiency and stability are similar, indicating that the solid-solid imprinting method can not only match the laboratory small-area battery preparation process, but can also be extended to the preparation of large-area perovskite films, which is conducive to future large-scale production.
[0109] Example 3 further verifies the above conclusions. This example uses solid-solid embossing to prepare a large area (effective area 1cm 2 ) perovskite solar cells, the device also showed a photoelectric conversion efficiency of 24.86% ( Figure 8 ).
[0110] Example 4 explored the reusability of the pyridine solid-state imprint layer. The same imprint layer was used to perform solid-solid imprint annealing on 30 perovskite films, and then the perovskite solar cells were assembled. The test results showed that all 30 devices showed excellent photoelectric conversion efficiency ( Fig. 9 , 25% to 26%). This indicates that in each imprinting process, the solid imprinted molecules can selectively interact with the perovskite, rather than being imprinted indiscriminately on the perovskite film. This selectivity can avoid ineffective molecular coverage and improve the passivation effect of film defects. At the same time, it can also improve material utilization and reduce device manufacturing costs.
[0111] Examples 5, 6 and 7 investigated the effects of solid-solid imprint annealing on different perovskite systems (MAPbI3, Cs x FA 1-x PbI3、MA x FA 1-x Pb(I y Br 1-y )3) and found that the crystallinity and microstructure of the perovskite were similar to those of the perovskite prepared in Example 1, and the film quality was significantly improved ( Fig.10 ), indicating that the solid-solid imprinting method adopted in the present invention is not limited by the perovskite component system and has good universality.
[0112] In summary, the present invention provides a solid-solid imprint annealing process, which can simultaneously achieve uniform and dense growth of perovskite crystals in a confined space and defect passivation, effectively improve the quality of perovskite films, and further improve the photovoltaic performance of perovskite solar cells. This method can effectively avoid the structural degradation of perovskite wet films due to surface defects during traditional annealing, while passivating various defects in perovskite films, improving interface energy level structures, and enhancing carrier transport capabilities, thereby improving the efficiency and stability of the device. In addition, the solid-solid imprint annealing process in the present invention is simple, and the solid passivation layer can be reused multiple times, which is suitable for large-area perovskite solar cells with different component systems, and has high universality and commercial application prospects.
[0113] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for improving the quality of polycrystalline perovskite crystals by solid-solid imprint annealing, characterized in that: First, a solid imprint layer of pyridine molecules is prepared, and then the solid imprint layer is covered on the surface of the perovskite wet film at the initial stage of perovskite annealing, and annealing is performed under certain pressure and temperature conditions until the annealing process is completed.
2. The method for improving the quality of polycrystalline perovskite crystals by solid-solid imprint annealing according to claim 1, characterized in that: The N and (CH2) in the pyridine molecule x NH2 is in the adjacent position, and any one of 2-aminopyridine, 2-aminomethylpyridine, and 2-(2-aminoethyl)pyridine is selected.
3. The method for improving the quality of polycrystalline perovskite crystals by solid-solid imprint annealing according to claim 1, characterized in that: The initial annealing period is 1 to 5 minutes from the beginning of annealing, the annealing temperature is 120 to 150° C., the total annealing time is 10 to 30 minutes, and the pressure is 0.049 to 0.1225 MPa.
4. The method for improving the quality of polycrystalline perovskite crystals by solid-solid imprint annealing according to claim 1, characterized in that: The specific steps include: 1) Processing conductive glass: cutting the conductive glass into required sizes and cleaning it for later use; 2) Preparing a tin dioxide electron transport layer: preparing a raw material solution, and preparing a tin dioxide film on the glass treated in step 1) by a chemical bath deposition method; 3) preparing a pyridine solid imprint layer: preparing a pyridine isopropanol solution, coating a pyridine molecular layer on the glass surface treated in step 1), and then performing an annealing treatment; 4) Preheating of the stamping weight: Place the weight on a hot table for preheating; 5) Preparing a perovskite film: preparing a perovskite precursor solution, and dropping it onto the substrate treated in step 2) to prepare a wet film; 6) Solid-solid imprint annealing: Under heating conditions, the pyridine solid imprint layer prepared in step 3) is covered on the upper surface of the perovskite film, and then the weight preheated in step 4) is pressed on the covering layer. Solid-solid imprinting is performed at the beginning of perovskite annealing until the perovskite annealing is completed, and the imprint layer is removed.
5. The method for improving the quality of polycrystalline perovskite crystals by solid-solid imprint annealing according to claim 4, characterized in that: Also includes: 7) Preparation of Spiro-OMeTAD hole transport layer: Prepare a Spiro-OMeTAD chlorobenzene solution, apply it on the perovskite film prepared in step 6), and then place the film in a constant temperature and humidity drying oven for oxidation treatment; 8) Preparation of metal counter electrode: Depositing a metal counter electrode with high work function on the Spiro-OMeTAD film treated in step 7) by vacuum thermal evaporation.
6. The method for improving the quality of polycrystalline perovskite crystals by solid-solid imprint annealing according to claim 5, characterized in that: The conductive glass in step 1) is selected from any one of ITO, FTO, PET / ITO, and PEN / ITO; the cleaning step of the conductive glass includes: The glass is ultrasonically cleaned with glass cleaning liquid, deionized water, acetone, ethanol and isopropanol in sequence, and then treated with a UV-ozone cleaning machine after drying; the ultrasonic cleaning time is 15 to 20 minutes; the UV-ozone cleaning machine treatment time is 15 to 30 minutes, and the temperature is 20 to 30°C.
7. The method for improving the quality of polycrystalline perovskite crystals by solid-solid imprint annealing according to claim 4, characterized in that: The preparation method of the raw material solution in step 2) is as follows: dissolve 2 g urea, 2 mL hydrochloric acid, 40 uL trifluoroacetic acid and 0.44 g SnCl2·2H2O in 160 mL deionized water; The chemical bath deposition method comprises the following steps: immersing the conductive glass substrate in a raw material solution, reacting the solution at 90° C. for 4 hours, taking out the glass, ultrasonically cleaning it with deionized water and isopropanol for 5 minutes respectively, then rinsing it with deionized water and ethanol, and then drying it with a nitrogen flow.
8. The method for improving the quality of polycrystalline perovskite crystals by solid-solid imprint annealing according to claim 4, characterized in that: The pyridine concentration in the pyridine isopropanol solution in step 3) is 0.08-0.42 mol / L, and the preparation method is: take an appropriate amount of pyridine molecules and dissolve them in 1 mL of isopropanol, and stir and mix them evenly; The pyridine isopropanol solution is applied to the glass surface treated in step 1) by spin coating or immersion; The spin coating method is as follows: 50uL of pyridine isopropanol solution is added dropwise to the glass surface for spin coating to form a film; the spin coating speed is 500-3000rpm, and the spin coating time is 30-50s; the immersion method is as follows: the glass is immersed in the pyridine isopropanol solution for 1-5min; The annealing temperature is 80-120° C., and the annealing time is 5 minutes.
9. The method for improving the quality of polycrystalline perovskite crystals by solid-solid imprint annealing according to claim 4, characterized in that: The weight in step 4) is a chrome-plated weight with a mass of 2 to 5 kg; the preheating temperature is 120 to 150° C. and the preheating time is 3 to 5 min; In step 5), the perovskite precursor solution is dripped onto the substrate treated in step 2), and a one-step anti-solvent method is used to spin-coat the substrate to form a film; wherein the spin-coating speed is 1000-5000 rpm, the spin-coating time is 10-50 s, and the anti-solvent is ether or chlorobenzene; The concentration of the perovskite precursor solution is 1.5-1.8 mol / L; the solvent system is a mixed solvent of DMF and DMSO, and the volume ratio of DMF:DMSO is 4:1-9:1; The perovskite component is any one of FAPbI3, MAPbI3, CsPbI3 or a ternary mixed perovskite.
10. The method for improving the quality of polycrystalline perovskite crystals by solid-solid imprint annealing according to claim 5, characterized in that: The preparation method of the Spiro-OMeTAD chlorobenzene solution in step 7) is as follows: 73.2 mg of Spiro-OMeTAD was dissolved in 1 mL of chlorobenzene and stirred for 1 h, and then 28.8 μL of 4-tert-butylpyridine and 17.6 μL of 520 mg mL -1 The solution of LiTFSI in acetonitrile was stirred for 1 h; The spin coating speed is 3000 rpm, the spin coating time is 30 seconds; the drying oven temperature is 20-25°C, the humidity is 10-20%, and the oxidation time is 20 hours; In step 8), the metal is Au or Ag; the evaporation rate is 0.005-0.2 nm / s, the evaporation temperature is 900-1000° C., the evaporation time is 20-30 min, and the electrode thickness is 60-90 nm.
Citation Information
Patent Citations
Spray coating solution, perovskite layer, preparation method of perovskite layer and perovskite cell
CN108057590A
Method and device for preparing perovskite single crystal thin film solar cell
CN108666428A
Easy-to-amplify perovskite surface passivation process
CN113161487A
Method for preparing efficient perovskite solar cell with assistance of pre-protonated aminopyridine
CN114388698A
Method for constructing organic-inorganic hybrid perovskite single crystal film surface patterning
CN115715137A